STRATEGI PENGEMBANGAN DANAU NAGA SAKTI MENJADI KAWASAN OBJEK WISATA DI KECAMATAN PUSAKO KABUPATEN SIAK - Dini Nanda Aprilia; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Tourism is one type of new industry that is able to generate rapid economic growth in the provision of employment, Siak regency is one area in Riau Province, known as the homeland of Malay culture, it is supported by various kinds of tourist objects such as nature tourism, History, culture and artificial tourism. One of them is the natural tourism object of Danau Naga SaktiTourism in Pusako District.The problems in this research are the factors that encourage and hamper the development of the attractions of Danau Naga Sakti, the development strategy undertaken by the Siak Regency Government in developing the attractions of Danau Naga Sakti and how big the contribution of the attractions of Danau Naga Saktimagic to the original income of Siak regency. This study aims to explore the development strategy And to know the potential of tourism that can be developed in the area of Danau Naga Sakti tourist attraction and also know the factors that influence the development of Danau Naga Sakti Tourism object in Pusako Subdistrict Siak Regency.The theory used is the management strategy of Elittan and Anatan and analyzed SWOT from Rangkuti. The research method used in this research is descriptive qualitative research method. Data collection is done by interview, observation and documentation. Data analysis technique used is Triangulation technique. Further analyzed by using SWOT analysis. From the research results can be seen that in developing the object of Danau Naga Sakti Tourism is done by using technology strategy, innovation strategy and operation strategy. Furthermore, SWOT analysis was conducted to find out what strategies are suitable for the development of this Danau Naga Sakti Tourist Attraction.Keywords: Tourism Object Danau Naga Sakti, Strategy, Tourism Development